FEATURES OF THE COMARBID COURSE OF IRRITABLE BOWEL SYNDROME AND BRONCHIAL ASTHMA IN CHILDREN WITH CONNECTIVE TISSUE DYPLASIA - Abdullaeva Dilorom T; Agzamkhodzhaeva Nasiba S (International Engineering Journal For Research & Development, 2022)
This article is a clinical study that revealed the commonality of phenotypic features characteristic of BA and IBS. We studied 112 children aged 5 to 18 years with bronchial asthma with connective tissue dysplasia: 43 of them had disorders of the gastrointestinal tract. Among the sick children we observed, it was noted that children are often exposed to various stressful situations both at home and in public groups (kindergartens, private and ordinary schools): misunderstandings of the lesson, failure to complete the assigned task, stress before exams, excessive susceptibility to the teacher's remarks or teacher, conflicts among peers. At the heart of the pathogenesis of bronchial asthma and irritable bowel syndrome, one of the factors that causes a significant trigger is a violation of the psychosomatic status.